Penguatan Kelembagaan Organisasi Siswa Intra Sekolah (Osis) di SMK Negeri 2 Gorontalo - Nggilu, Ariyanto; Mahmud, Ramli; Kartika, Intan Tiara; Alimun, Afriani (Penerbit Widina, Widina Media Utama, 2025)
The Intra-School Student Organization (OSIS) serves as a strategic platform for the development of students’ character and leadership skills. However, its management at SMK Negeri 2 Gorontalo still faces challenges, such as low student participation. This community service aims to strengthen the OSIS institution through a collaborative program involving lecturers, students, and the community, using an interactive socialization method based on Knowledge Transfer and Exchange (KTE). The activity consists of three main stages: (1) delivering theoretical material, (2) open discussion, and (3) interactive dialogue. The results of this community service show significant improvement in six key achievement indicators: (1) the committee’s understanding of OSIS functions increased from limited to comprehensive, (2) OSIS members’ participation, initially low, became more active, (3) creativity in designing work programs developed from monotonous to innovative, (4) communication and teamwork skills improved from ineffective to more open and coordinated, (5) social responsibility attitudes, previously lacking, are now evident in environmental care programs, and (6) the school’s support has become increasingly synergistic. In conclusion, this collaborative approach not only successfully revitalized OSIS’s role as a student leadership laboratory but also established a sustainable mentoring model that can be adopted by other schools. These findings reinforce that strengthening OSIS institutions requires systematic interventions integrating academic knowledge transfer with practical organizational experience in the field.ABSTRAKOrganisasi Siswa Intra Sekolah (OSIS) merupakan wadah strategis dalam pengembangan karakter dan kepemimpinan siswa. namun pengelolaannya di SMK Negeri 2 Gorontalo masih menghadapi kendala seperti rendahnya partisipasi siswa. Pengabdian ini bertujuan untuk memperkuat kelembagaan OSIS melalui program pengabdian kolaborasi Dosen dan Mahasiswa masyarakat dengan metode sosialisasi interaktif berbasis Knowledge Transfer and Exchange (KTE). Kegiatan ini mencakup tiga tahap utama: (1) penyampaian materi teoritis, (2) diskusi terbuka, dan (3) dialog interaktif. Hasil pengabdian menunjukkan peningkatan cukup mencolok pada enam indikator capaian: (1) pemahaman pengurus tentang fungsi OSIS meningkat dari terbatas menjadi menyeluruh, (2) partisipasi anggota OSIS yang awalnya rendah kini lebih aktif, (3) kreativitas perancangan program kerja berkembang dari monoton ke inovatif, (4) kemampuan komunikasi dan kerja sama tim yang sebelumnya kurang efektif menjadi lebih terbuka dan terkoordinasi, (5) sikap tanggung jawab sosial yang semula kurang terlihat kini tampak dalam program kepedulian lingkungan, serta (6) dukungan pihak sekolah yang semakin sinergis. Kesimpulan dari pelaksanaan pengabdian ini yaitu pendekatan kolaboratif ini tidak hanya berhasil merevitalisasi peran OSIS sebagai laboratorium kepemimpinan siswa, tetapi juga membangun model pendampingan berkelanjutan yang dapat diadopsi oleh sekolah lain. Temuan ini memperkuat bahwa penguatan kelembagaan OSIS memerlukan intervensi sistematis yang mengintegrasikan transfer pengetahuan akademik dengan praktik organisasi di lapangan.